Philosophical Perspectives on Music - Bowman, Wayne D. (Oxford Oxford University Press, 1998)
Designed to introduce music students and musicians to the vitality of music philosophical discourse, Philosophical Perspectives on Music explores diverse accounts of the nature and value of music. It offers an accessible, even-handed consideration of philosophical orientations without advocating any single one, demonstrating that there are a number of ways in which music may reasonably be understood. This unique approach examines the strengths and advantages of each perspective as well as its inevitable shortcomings.From the pre-Socratic Greeks to idealism, through phenomenology, and on to contemporary socio-cultural critiques, this wide-ranging survey examines the views of selected influential thinkers in sufficient detail to permit their voices to be personally and meaningfully experienced. Striving to portray philosophy as an intriguing dialogue rather than a dogmatic source of definitive answers, it invites readers to become full participants in an ongoing process of philosophical debate with vital contemporary relevance and extensive practical significance. Examining what music is, how it works, and what music is good for, this book encourages musicians to join in important conversations that shape both the ways they practice their art and the ways in which they and others understand it.Accessible to students with little or no background in music philosophy, Philosophical Perspectives on Music provides the foundation for applied or professional philosophies while also introducing readers to the richness of the philosophical quest. Ideal for philosophy of music and philosophy of music education courses, it is also enlightening reading for students of musicology, music theory, and music performance. Featuring interdisciplinary dialogue, this insightful text addresses issues common to the concerns of all musicians.
Keywords: Music philosophy and esthetics